Einfallstor in die Sowjetunion : Die Besatzung Deutschlands und die Ausspähung der UdSSR durch den britischen Nachrichtendienst - Maddrell, Paul (Vierteljahrshefte für Zeitgeschichte, 2003)
The conquest of Eastern Germany by the Soviet Union in 1945 presented Britain with a threat to its security but also with excellent opportunities for gathering intelligence. Soviet exploitation of weapons factories and scientific and technical personnel in the Eastern Zone meant that Germans had knowledge of the USSR's armaments build-up; they could be recruited as spies. Soviet army officers and scientists could be exploited for intelligence if they defected to the West, which was much easier after 1945 than before. German prisoners-of-war used as forced labourers in the USSR's post-war reconstruction could be interrogated to find out what they knew about it. German scientists, engineers and technicians deported to the USSR in the years 1945-48 could, on their return to Germany, be interrogated for their knowledge of Soviet weapons development. So the main intelligence assets of Britain and the USA in the period 1945-61 were the division and exploitation of Germany; the two countries further increased the benefit they derived from these by sharing much of the intelligence which they gathered in Germany. Exploitation of these sources allowed the first intelligence penetration of the USSR to be made and also contributed to the later intelligence successes achieved by the U-2 spyplane and Corona satellite reconnaissance programmes. (Vierteljahrshefte für Zeitgeschichte / FUB)